Perlindungan Hukum Terhadap Anak yang Diterlantarkan - Utami, Rifka Aulia; Jumadi (Alauddin Law Development Journal (ALDEV), 2023)
Children are a mandate and a gift from Almighty God, which is inherent in their dignity and their dignity as a whole human being. Children need special handling, but not all parents who sincerely accept children and give love. Parents sometimes don't care about parents' lack of care and affection for their children. Few parents accept disabled children with a sincere heart. This has caused many cases of parents who have abandoned their children. The method of this research is a normative legal research aiming to find and formulate legal arguments, through the analysis of the main problem. The technique of collecting legal documents is done by studying literature. The approach used in this study is the statutory approach, in particular by examining the legal rules applicable with regard to the legal protection of children abandoned by their parents. Interviews were conducted at the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in the city of Makassar, as support and to refine the normative analysis.